Performance of watermelon cultivars for the “Vertente Goiana do Paranaíba” micro-region - Cunha, Victor Manoel Witis Carvalho; Coutinho, Givago; Dias, Rita de Cassia Souza (Revista de Ciências Agroveterinárias, 2025)
Watermelon (Citrullus lanatus Thumb.) is a crop of great socioeconomic importance, especially for family farmers, due to its low production costs and ease of management. In Brazil, the most widely planted cultivar is Crimson Sweet and similar cultivars, accounting for over 90% of the supply to the consumer market. In this sense, diversification is necessary, offering more crop options to producers that can serve different market niches. In this context, this study aimed to identify watermelon cultivars with productive potential for the "Vertente Goiana do Paranaíba" micro-region. The research was conducted at the University Center of Goiatuba, which has a predominantly semi-humid tropical climate, with average annual rainfall between 1,500 and 1,800 mm. Four cultivars were evaluated, with each cultivar considered a treatment. The work was conducted in randomized blocks with five blocks, totaling 20 experimental plots. Each experimental plot had six plants. The analysis of variance revealed significant differences in the physical characteristics of the fruits, such as longitudinal diameter, transverse diameter, and peel thickness. The Crimson Sweet cultivar stood out for its higher fresh weight and productivity, results that are largely due to the cultivar’s inherent characteristics. Next, the cultivars ’BRS Kuarah’ and ’Sugar Baby’ were ranked highest in these criteria, respectively. The Sugar Baby weighed slightly less than the minimum required by supply centers, which is two to three kg. There was no difference in the duration of the production cycle (days) and soluble solids content (°Brix) between cultivars, demonstrating the possibility of crop diversification and the potential for exploring new cultivars in the region, especially ‘BRS Kuarah’ and ‘Sugar Baby’.